Occurrence, Removal and Bioaccumulation of Perfluoroalkyl Substances in Lake Chaohu, China - Pan, Xu (Int J Environ Res Public Health, 2019)
The perfluoroalkyl substances (PFAAs) have received growing attention in recent years as emerging contaminants in the aquatic environment. The occurrence, removal and bioaccumulation of fourteen PFAAs (C4–C14 carboxylate; C4, C6, C8 sulfonates) were investigated in Lake Chaohu, China. The concentrations of the selected PFAAs in inflowing river, lake water and sewage treatment plant (STP) samples were analyzed by ultra performance liquid chromatograph (UPLC–MS/MS). The results showed that perfluorohexanesulfonic acid (PFHxS), perfluorobutane sulfonate (PFBS), perfluorobutyric acid (PFBA) and perfluoropentanoic acid (PFPeA), instead of perfluorooctanoic acid (PFOA), were predominant PFAAs in the inflowing river and lake water with maximum concentrations in the ranges of 52.2–1866 and 27–236 ng L(−1), respectively. The highest concentrations of total PFAAs were detected in the western rivers. The effluents from seven STPs were likely important sources of PFAAs in surface water, and the amount of the daily fluxes in the effluent were 132 g for short-chain PFAAs and 109 g for long-chain PFAAs. PFAAs were widely detected in Chinese icefish (Neosalanx tangkahkeii taihuensis) collected from Lake Chaohu, with maximal concentrations ranging from 1.79 ng g(−1) to 50.9 ng g(−1). The logarithmic bioaccumulation factors of perfluorodecanoic acid (PFDA, 3.5), perfluorooctane sulfonate (PFOS, 3.35) and perfluorononanoic acid (PFNA, 3.31) indicated the bioaccumulation of these long-chain PFAAs. This study is useful for enhancing our understanding of the pollution profiles of PFAAs and their environmental health risk in the freshwater lake.